Reflexão sociológica sobre a produção do patrimônio cultural brasileiro - Prado, Marla Michelle Nascimento Portela do (2013)
We dedicate this macro sociological research production of cultural heritage with the application of theoretical and methodological assumptions of Pierre Bourdieu's field concepts. In this exercise of reflexive sociology, we probe the theoretical possibilities of the tool and simulataneously contextualize cultural heritage with a commitment to demonstrate the validity of theoretical and methodological appropriation. This leads us to investigate the production trajectory of their training and autonomization in social structure. Justified by Bourdieu's production theory, which works as a field, we follow him in investigating the construction of its social structure and boundaries. By this logic, individuals actively participate in structuring with limited field. Within conditions of unequal power and differing forms of appropriation for objective realities, individuals build hierarchies where competing positions are constructed values of legitimacy. Therefore, in this study, we use a retrospective approach in claiming production as a field, and a perspective of investigation on logic in the social structure. With reflection, we demonstrate that the participation of individuals in political negotiation produces cultural heritage.